Molecular Dynamics Simulation of Heparin 8 and 12 Saccharides With 2S Sulfation Pattern and 1C4 Iduronate Conformation To FGF2-FGFR1 Ternary Complex As Environmentally Friendly Anticancer Drug Candidate Discovery - Barroroh, Himmatul; Mazyadi, Muhammad; Hakim, Lukman; Safitri, Anna; Widodo, Widodo (The Journal of Pure and Applied Chemistry Research, 2026)
Heparin is a linear polysaccharide composed of repeating 1–4 linked units of iduronic acid and glucosamine and is widely used as an anticoagulant drug. This paper reports characteristics of three-dimensional structural changes and stability of the FGF2–FGFR1 ternary complex in the presence of heparin 8- and 12-saccharide fragments with a 2S sulfation pattern and ^1C₄ iduronate conformation using in silico approach. Study was performed using molecular docking followed by 100 ns molecular dynamics (MD) simulations. Heparin 8- and 12-saccharide ligands were docked to the FGF2–FGFR1 ternary complex, then was evaluated by MD using GROMACS to monitor backbone root mean square deviation (RMSD), residue root means square fluctuation (RMSF), and key residue interactions over time. Docking suggested a more favorable initial binding energy for the 8-saccharide ligand, whereas MD revealed that the 12-saccharide ligand more effectively maintained stable interactions between FGF2 and FGFR1, as indicated by lower backbone RMSD at the end of the simulation and more persistent contacts at basic residues in the heparin-binding sites of both proteins. These dynamic stability features provide a mechanistic explanation for previously reported in vitro findings, showing that 12-saccharide 2S heparin fragments exert stronger FGF2-dependent antiangiogenic and anticancer effects than shorter fragments, thereby supporting their potential as environmentally friendly anticancer drug candidates.